I am Spiritual but Not Religious: Reconstructing Da’wah Communication to Re-Engage Generation Z in the Contemporary Digital Era - Abdul Hamid; Deni Rahman (Ikatan Sarjana Komunikasi Indonesia, 2026)
In the contemporary digital era, many Generation Z Muslims identify as “spiritual but not religious,” affirming faith while distancing themselves from rigid institutional authority. Meanwhile, Islamic da’wah communication often remains hierarchical and one-directional, creating a gap between institutional messaging and digitally embedded youth. This study reconstructs da’wah communication strategies to re-engage Generation Z by aligning communicative practices with their digitally shaped spirituality, authority evaluation, and participatory expectations. Using a qualitative design, data were collected from 27 Muslim university students in urban Indonesia through semi-structured interviews, digital observation, and documentation of online da’wah content over three months. The data were analyzed using thematic coding through iterative reduction, categorization, and verification. Findings show that participants maintained commitment to Islamic values but expressed spirituality in individualized, selective, and digitally mediated ways. Religious authority was evaluated primarily through authenticity, transparency, and responsiveness rather than institutional status. Dialogical, short-form, and visually engaging content was most effective in sustaining trust and attention. These results indicate that da’wah communication must shift toward participatory, authenticity-centered, and digitally adaptive models. This reconstruction offers a theoretical and practical framework for engaging Generation Z meaningfully in contemporary digital religious environments today.